Remission of Thymoma on Steroid Therapy in a Patient With Atypical Thymoma-Associated Multiorgan Autoimmunity: A Case Report and Literature Review - Wrona, Ewa; Dębska-Szmich, Sylwia; Pastuszka, Marta; Braun, Marcin; Czyżykowski, Rafał; Potemski, Piotr (Frontiers in Immunology, 2021)
In up to 34% of cases, thymoma, itself a rare neoplasm, is accompanied by autoimmune disorders, two of which are thymoma-associated multiorgan autoimmunity (TAMA) and paraneoplastic autoimmune multiorgan syndrome (PAMS). Unfortunately, differential diagnosis between these two entities can be challenging since no strict PAMS definition exists and PAMS can overlap with a subgroup of TAMA patients with skin lesions as leading presentation. We present a case of a 68-year-old woman with a diagnosis of thymoma accompanied by myasthenia gravis, hypothyroidism and GvHD-like mucocutaneous lesions that initially could account to both TAMA and PAMS diagnosis. However, following the exclusion of humoral autoimmunity against components of epithelial cells junction, TAMA was finally established. Interestingly, the introduction of corticosteroid therapy for TAMA symptom management resulted in unexpected partial remission of thymoma with no impact on mucocutaneous lesions. Our case study is an example of two extremely rare phenomena accompanying thymomas: unprecedented TAMA presentation with GvHD-like mucositis, which as we postulate should be placed in the spectrum of TAMA, and tumor remission on steroids.